2005
DOI: 10.5014/ajot.59.5.546
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Disability Studies Concepts Into Occupational Therapy Education Using Service Learning

Abstract: This article describes an occupational therapy educational program's experience with service-learning courses that has fostered student learning about service to the community and disability as a multidimensional construct. Faculty-reflective perspectives about disability and ways to enhance learning about disability as a human experience are presented as an important consideration for health care education curriculum design and course development. Through review of educational evaluation described in research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…With increased emphasis on producing culturally sensitive OTD professionals, service learning projects in a crosscultural setting as a pedagogy extend beyond skill development (e.g., wheelchair fittings) to building coping strategies for interacting with clients (metacognitive CQ), enhancing knowledge of culture (cognitive CQ), persisting to overcome any cultural barriers (motivational CQ), and building the behavioral repertoire (behavioral CQ) of occupational therapists. Findings associated with this study build on Gitlow and Flecky's (2005) findings that service learning facilitates a more complete comprehension of the client beyond immediate occupational therapy needs to the influence of the client's culture and associated constructs, reinforcing that service learning improves confidence to seamlessly interact with diverse clients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increased emphasis on producing culturally sensitive OTD professionals, service learning projects in a crosscultural setting as a pedagogy extend beyond skill development (e.g., wheelchair fittings) to building coping strategies for interacting with clients (metacognitive CQ), enhancing knowledge of culture (cognitive CQ), persisting to overcome any cultural barriers (motivational CQ), and building the behavioral repertoire (behavioral CQ) of occupational therapists. Findings associated with this study build on Gitlow and Flecky's (2005) findings that service learning facilitates a more complete comprehension of the client beyond immediate occupational therapy needs to the influence of the client's culture and associated constructs, reinforcing that service learning improves confidence to seamlessly interact with diverse clients.…”
Section: Discussionmentioning
confidence: 99%
“…Gitlow and Flecky (2005) found that a service learning experience involving a community project investigating accessibility issues impacted students' conceptualization of the individual, environmental and social constructs of disability. Furthermore, the quantitative data from the study revealed that more than 90% of the participating students increased their personal comfort level in working with individuals from different cultures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This perspective replaced the historical view of impairment or disability as stemming from the person-environment relationship with an emphasis on physiological impairment as located within the person [3]. Following this, major occupational therapy leaders called for a return to the holistic, humanistic foundation of the profession [4,5], which translated into the development of client-centered approaches as best practice, and reclaimed the biopsychosocial model as the basis for occupational therapy practice [1]. While presently, occupational therapy tends to see itself as operating based on a client-centered approach which reflects the notion of collaboration with the service user [10], research often reflects a discrepancy between rhetoric and actual practice favoring the medical model, as viewed by service users and reflected in occupational therapy clients' narratives [3,6,7].…”
Section: Brief Review: Occupational Therapy and Disabilitymentioning
confidence: 99%
“…Although historically occupational therapy's view of disability reflects a holistic approach based on humanism and moral treatment [1,2], the 1950s and early 1960s ushered in a paradigm strongly rooted in the medical model. This perspective replaced the historical view of impairment or disability as stemming from the person-environment relationship with an emphasis on physiological impairment as located within the person [3].…”
Section: Brief Review: Occupational Therapy and Disabilitymentioning
confidence: 99%
See 1 more Smart Citation